Self-forgiveness in the Person Who Has Committed Child Sexual Abuse - Prieto Ursúa, María Inés; San Martín Caballero, Sonia Xianzi (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
The process of self-forgiveness becomes difficult when our behavior has harmed another in a very intense and unjust way and is dissonant with our values or principles. This experience threatens one’s own identity, and sets in motion self-protection mechanisms to maintain an acceptable self-concept. From an individual approach and drawing on the contributions of the psychology of forgiveness, the article offers keys to understanding the process of self-forgiveness in the perpetrator of child sexual abuse (CSA): it briefly reviews the extent of the harm inflicted, to understand the difficulty of the task and the defenses and resistances present during the process, presents in detail two protection mechanisms frequently present in CSA perpetrators and ends by identifying the steps in the process of self-forgiveness that would allow the perpetrator to rebuild an acceptable identity from the full recognition of the offence and his responsibility.